Failure analysis of hybrid scarf joints - Toh, Zi Ying (2019)
The use of composite materials has become increasingly popular in industries such as modern aviation. For instance, in the aerospace sector, composites are used for their lightweight, resistance to corrosion and fatigue, these conditions are preferable for semi-monocoque aircraft structures. In addition, traditional sheet metal construction tends to lose material strength at elevated temperatures, while composites are capable of withstanding high temperatures and thermal expansion without compromising material properties. Strong reinforcements such as Glass Fiber Reinforced Plastics (GFRPs) has helped meet the design features of modern aircraft bodies. A critical feature to consider however is the application of these composites on the fuselage. This can be done by conventional mechanical joints or the innovative use of adhesively bonded joints. Adhesively bonded joints are known for factors such as its material compatibility, ability to form large complex geometries and its lower fabrication costs, it also offers more alternatives over traditional joint techniques. This report evaluates the performance of adhesively bonded scarf joints and hybrid scarf joints; which is a combination of adhesively bonded joints and fasteners. Purpose of incorporating mechanical fasteners is to ensure a fail-safe design feature and provide residual strength to the joint as the adhesive experience failure. Four main joint configurations were tested to observe the effects of varying the fastener layout on the respective failure modes and overall load bearing capacity of the joint. Stiffness and strain analysis were drawn from the results of quasi-static tensile testing conducted on all the joint configurations. Experimental results were compared across the different joint configurations to determine the highest strength, potential failure modes and suitability of such joint techniques on loaded structures.